Implementation of Sustainability Business Practices Based on Tri Hita Karana Values in International Chain Hotels in Bali - Wiryanata, I Gusti Ngurah Agung; Susanti, Christina; Sumariati, Dewa Ayu Rai; Septiviari, Anak Agung Istri M. (Jurnal Ekonomi Kreatif dan Manajemen Bisnis Digital, 2025)
The purpose of this study is to analyze sustainability business practices based on Tri Hita Karana (THK) in hotels under the auspices of the Marriott international network, namely E Hotel in Ubud, S Hotel in Kuta, W Hotel in Seminyak, TS Hotel in Legian, and TL Hotel in Nusa Dua. This qualitative research uses informants determined by purposive sampling techniques. Interviews, documentation studies, and observation were used in data collection. The data analysis technique used in this study is an interactive model by Miles and Huberman, which consists of data reduction, data presentation, and conclusions. The findings indicate that each hotel adapts Marriott International's sustainability standards aligned with THK's core principles: Parahyangan (harmony with God), Pawongan (harmony among people), and Palemahan (harmony with nature). The hotels participate in activities such as religious engagement, food redistribution, waste segregation, energy conservation, and the use of eco-friendly products. This integration of THK enhances employee engagement, strengthens community relationships, and promotes environmentally responsible practices in the hospitality industry.